Auction Quotas with a Foreign Duopoly - Tan, Ling (IMF Working Papers; Working Paper ;, 2000)
This paper uses a partial equilibrium framework to compare the welfare consequences of different methods of quota administration relative to free trade under imperfect competition. It shows that a country importing a good from foreign duopolists may improve its welfare by setting a quota at the free trade quantity and giving a fraction of the quota licenses to the duopolists while auctioning off the rest.